(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Objective: To review current concepts in the management of subclinical hypothyroidism (SCH) in patients with non-specific symptoms. Data sources: A review of articles reported on overt hypothyroidism and subclinical hypothyroidism. Summary of review: In a patient with primary overt hypothyroidism, management is usually straightforward: treatment with thyroxine should be offered to anyone with characteristic clinical features, a raised serum thyroid stimulating hormone (TSH) concentration and a low serum thyroxine (T4) concentration. More difficult is the management of a patient with subclinical hypothyroidism (SCH), in whom serum TSH is slightly raised (5-20 mIU/L) but T3, T4 levels are normal, and who is either asymptomatic or has only non-specific symptoms. Left untreated, some of these patients will eventually develop overt hypothyroidism. This review will address the use of thyroxine in patients with subclinical hypothyroidism. DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i3.21045